2021
DOI: 10.1088/1361-6552/abf69d
|View full text |Cite
|
Sign up to set email alerts
|

Error analysis in measuring physical quantities using various sensors on a smartphone

Abstract: In the initial topic in basic physics in school and college, the concept of analysing a measurement error needs to be understood by students. This paper proposes the use of various sensors on smartphones for statistical error analysis which usually uses the classical method with repeated measurements. The smartphone sensors used were light, acceleration, and magnetometer sensors. The data from the sensor recording fluctuations for 10 s were analysed for the simple statistical figures and error. The experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The example by Countryman deployed accelerometers as a case study for the axis orientation and microelectromechanical system (MEMS) [6]. Errors of smartphone-based measurements can ISSN: 0067-2904 be analyzed and demonstrated in the case of accelerometers, magnetometers, and ambient light sensors [9]. Hochberg et al reported the positive effects on students learning physics using smartphones [7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The example by Countryman deployed accelerometers as a case study for the axis orientation and microelectromechanical system (MEMS) [6]. Errors of smartphone-based measurements can ISSN: 0067-2904 be analyzed and demonstrated in the case of accelerometers, magnetometers, and ambient light sensors [9]. Hochberg et al reported the positive effects on students learning physics using smartphones [7][8].…”
Section: Introductionmentioning
confidence: 99%
“…One technology that is widely used for remote physics experiments is a smartphone. Smartphones provide many censor features such as light, acceleration, magnetometer, pressure, and gyroscope censors [3][4][5][6]. Most of the experiments developed are on the topic of mechanics [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%